Helmholtz resonators with more than one opening - Dosch, Hans Günter; Hauck, Matthias (European journal of physics, 2021)
Helmholtz resonances have been investigated extensively and are still of scientific interest, they are also commonly used in the field of physics education. In this paper, we investigate for the first time systematically resonators with several openings and compare our results with theories taking into account radiative interactions. The presented experiments and possible extensions of them are well suited for classroom demonstrations and student projects.